Regulating Legal Assistant Practice: A Proposal That Offers Something for Everyone - Daniel R. Ray (Washington University Journal of Law & Policy, 2003)
The premise of this Article is straightforward: let’s regulate legal assistants, let them handle more lawyer stuff, and everyone will benefit. “Lawyer stuff” means activities that constitute the practice of law. My purpose here is not to add to the extensive scholarship that explains and debates the “practice of law” or its ugly stepchild, the “unauthorized practice of law.” Nor is it my purpose to consider all of the many policy issues surrounding those topics that make for lively bar dinner debate. In an effort to build upon existing scholarship, I offer a regulatory model intended to accommodate the interests of all concerned. More precisely, this proposal balances the public’s interest in being able to choose among legal service providers against other public interests, lawyer interests, and legal assistant interests. The proposal strikes this balance by combining a competency-based legal assistant registration system with the lawyer regulation and legal assistant supervision infrastructure already in place in every state. The proposal will be easy and inexpensive to implement and administer, and it is flexible enough to allow for state-to-state variations.
Keywords: Legal assistants; Recording and registration; Unauthorized practice of law; States